(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the didactic potential of artificial intelligence (AI) technologies in foreign language teaching, with a particular focus on English language instruction. It explores how AI-powered interactive platforms, automated assessment systems, personalized learning trajectories, and communication-based intelligent agents can enhance the effectiveness of language education. The study emphasizes the role of AI in the educational process and its pedagogical integration into foreign language teaching.